Property market bubbles : some evidence from Seoul and Hong Kong - Xiao, Qin (2008)
Expectations are central to real-estate price formation, making speculative bubbles an inherent feature of real-estate markets. The literature has developed an array of tools on the detection of bubbles. Unfortunately, because of identification problems, none of them alone can give a definitive answer to the question, “Is a bubble in the asset price of concern?” In this thesis, the author will look at the property markets in Seoul and Hong Kong and present evidences of bubbles by examining the problem with various tools. More specifically, the Markov-switching ADF test will be used to verify the existence of a bubble; the Kalman filter to extract missing fundamentals, thus infer the magnitude of a bubble; and the power-law-log-periodicity theory to predict the future trajectory of a bubble. The last method is free of the identification problems plaguing the literature. All three approaches point to the existence of bubbles in the markets examined.